Transition metal-free formal hydro/deuteromethylthiolation of unactivated alkenes. Issue 18 (20th April 2021) - Chen, Shuangyang; Wang, Jia; Xie, Lan-Gui
Abstract : A transition metal-free and methanethiol-free formal hydro/deuteromethylthiolation of unactivated alkenes has been developed. Abstract : Methylthioether is involved in the methylthiotransfer process in organisms, and therefore its functionality is of paramount importance to living organisms. Several methods for the installation of the methylthio group in small molecules have been reported previously; however, procedures starting from unactivated alkenes are rare. Herein, we report a formal hydro/deuteromethylthiolation of alkenes by using dimethyl(methylthio)sulfonium trifluoromethanesulfonate as the stimulator and sodium borohydride/deuteride as the hydrogen/deuterium source. The process represents a mild, transition metal-free and methanethiol-free route towards the synthesis of methylthioethers from unactivated alkenes.